A corpus investigation: the similarities and differences of cute, pretty and beautiful - Tan, Hai Ly; Chae, Kwan Jung (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
Since the introduction of computers in corpus linguistics, analyses of language has transformed into a more reliable guide to language than native speaker intuition. When disagreements between speakers’ intuition arise over the meaning and usage of words, an analysis of corpora can provide further insight on the characteristics of the words in question. In this study, a corpus analysis is conducted to investigate the similarities and differences in the use of cute, pretty and beautiful using the Bank of English (BoE). The investigation specifically looked at the frequency, collocation, semantic preference, semantic prosody and phraseology of the adjectives. The results show that similarities found between pretty and beautiful, according to these aspects, indicate that these two words may be the most synonymous pair of the three. However, the findings suggest that pretty and beautiful are far from being completely synonymous and do not have the same usage in all contexts. The analysis demonstrates that uncertainties a speaker may have regarding language use may be clarified by referring to corpora.